INFLUENCE OF 5,7-DIMETHOXY COUMARIN ON ADIPOGENESIS IN HIGH GLUCOSE INDUCED INSULIN RESISTANT 3T3-L1 ADIPOCYTES - J. JOHN ROBERT; R. SARUMATHI; C. SANKARANARAYANAN (The Bioscan, 2025)
Insulin resistance in adipocytes disrupts whole-body metabolic homeostasis contributing to various complications. This study investigates the adipogenic potential of 5,7-dimethoxy Coumarin (5,7-DMC) in high glucose-induced insulin resistance in 3T3-L1 cell lines. Insulin resistance was induced in 3T3-L1 adipocytes by exposing with 25 mM glucose and 0.6 nM insulin for 24 hours. The IC₅₀ value of 5,7-DMC was determined using the MTT assay. The cells were divided into four groups: Group I – Normal control (3T3-L1 adipocytes), Group II – Diabetic control (IR-3T3-L1), Group III – Diabetic cells treated with 5,7-DMC (60 μM), and Group IV – Diabetic cells treated with rosiglitazone (0.1 μM). Glucose uptake, intracellular triglyceride levels, and glycerol-3-phosphate dehydrogenase activity were evaluated in experimental groups. IR-3T3-L1 adipocytes exhibited reduced glucose utilization, lower triglyceride content and decreased dehydrogenase activity. Treatment with 5,7-DMC significantly improved these parameters, indicating enhanced insulin sensitivity. Oil Red O staining further confirmed increased triglyceride accumulation in treated cells. Molecular docking revealed a strong interaction between 5,7-DMC and Peroxisome Proliferator-Activated Receptor gamma (PPARγ), with a binding energy of –6.6 kcal/mol, comparable to rosiglitazone. These results suggest that 5,7-DMC improves insulin sensitivity in adipocytes offering therapeutic value in the management of diabetes mellitus.